The Role of the Performance of the Official Media Spokesperson in Shaping the Image of the Official Institution: From the Perspective of Jordanian Journalists - Qattash, Anas Fayz; Oreqat, Ahmad Ali (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to identify the role of the official media spokesperson in shaping the image of the official institution from the perspective of Jordanian journalists. Methods: This study is descriptive in nature and adopts a survey methodology by distributing a questionnaire to sectoral journalists. The study sample consisted of 56 individuals purposively selected. Results: The key findings of the study indicate that the official media spokesperson is considered a reliable source of information and news for journalists. Additionally, there is a lack of understanding between the official media spokesperson and journalists. The study also found that the failure of officials in the official institution to recognize the importance of the role of the official media spokesperson leads to a weakened performance, which negatively impacts the official institution. Furthermore, the results indicated that the official media spokesperson does not have a good degree of freedom in statements. One of the notable findings of the study was that the official media spokesperson requires training and preparation on how to interact with journalists. Conclusion: The study concludes that the role of the media spokesperson on behalf of the institution plays a significant role in shaping its image among the public. The importance of the role of the official media spokesperson in official institutions lies in granting them significant freedom in statements and providing information to journalists and media outlets, in addition to implementing relevant interactive programs to enhance interaction and communication between the official media spokesperson and journalists.